Sexual Dysfunction, Marital Adjustment, and Quality of Life Among Male Persons with Alcohol Dependence Syndrome Attending Tertiary Healthcare Institution in Northeast India: A Cross-Sectional Study - Bubul Sarkar; Arif Ali; Fayaz Ahmad Paul (Journal of Psychosexual Health)
Background: Sexual dysfunction is one of the major problems associated with the chronic use of alcohol. Sexual dysfunction is also significantly associated with marital adjustment and quality of life. Aim and Objectives: To determine the prevalence of sexual dysfunction and its association with marital adjustment and quality of life among persons with alcohol dependence syndrome (ADS) and to compare with the healthy control group. Materials and Methods: The present study used a cross-sectional, comparative, and descriptive research design. A purposive sampling technique was used to select the sample of 128 (64 patients with ADS and 64 healthy control persons) between the ages of 21 and 50, from the Department of Addiction Medicine, LGB Regional Institute of Mental Health (LGBRIMH), Tezpur, Assam. Sociodemographic and clinical data sheet, the Arizona Sexual Experience Scale (ASEX), the Severity of Alcohol Dependence Questionnaire (SDAQ), the Alcohol Use Disorders Identification Test (AUDIT), the International Index of Erectile Dysfunction (IIED), and The Drug Abuse Screening Test scales (DAST) were used. Results: The study revealed a higher prevalence of sexual dysfunction in the ADS group (64%) compared to the healthy control group (35.9%) (Chi-square = 46.916; p < .001). Marital satisfaction was significantly lower in the ADS group than in the healthy control group (Fisher’s exact test = 76.932; p < .001). Quality of life was also diminished in the ADS group, particularly in the physical ( t = −5.310; p <.001), social ( t = −4.481; p < .001), and environmental domains ( t = −4.250; p < .001). Furthermore, sexual dysfunction exhibited a significant negative correlation with marital adjustment ( r = −0.676; p < .01) and all domains of quality of life [physical domain ( r = −0.235; p < .001), social domain ( r = −0.383; p < .001), and environmental domain ( r = −0.383; p < .001)]. Conclusion: The prevalence of sexual dysfunction and erectile dysfunction was high in persons with alcohol dependence syndrome as compared to the healthy control group and it has a relationship with marital adjustment and quality of life. The findings highlight the importance of screening and evaluating sexual dysfunction in individuals with alcohol dependence. Comprehensive pharmacological and nonpharmacological services are warranted to address the unique needs of this population, promoting both recovery from alcohol dependence and improvement in overall quality of life.